PENERAPAN LITERASI MEDIA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Munandar, Aris; Sobari, Teti; Latifah, Latifah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This reseacrh is based on the lack of student interest in learning Indonesian, both from the material side and the teacher in providing material in the classroom. This is the concern of all of us, especially prospective educators, so that they are able to stimulate and stimulate students so that they can be more active and enjoy learning Indonesian. Media literacy is one solution to this problem, where teachers must be able to innovate by applying media literacy when learning Indonesian. This research is intended to find out prospective educators regarding their preparation for entering the world of education, thus learning cannot be sparated from the existence of innovation, on of which is the learning media that teachers must use. This study uses a qualitative descriptive method that describes data and facts in the from of descriptions  obtained through a questionnaire. The sample of this research was conducted on 10 students of IKIP Siliwangi. The results showed that of the entire sample, 10 students of IKIP Siliwangi knew about media literacy, 10 people said that the use of media literacy is appropriate for learning Indonesian, 10 people stated that media literacy can improve the quality of student learning, 9 people said that media literacy can be used at all levels of schooll and 1 person stated that media literacy cannot be used at all levels of schooll, and 3 people stated that conventional media is more effective than electronic and 7 people said conventional media was not effective than electronic media.